Innovative E-Module for Poetry: Enhancing Reading Skills in High School Student - Andika, Reta; Arono, Arono; Trianto, Agus (UNIB Press, 2025)
Various innovations in current learning are still less able to improve the quality of learning including in the development of teaching materials in the form of modules. Therefore, this research was conducted in research and development of teaching materials as an effort to develop a product for use. The purpose of this study was designed to describe the results of the needs analysis, design, implementation, and evaluation of teaching materials for class X. This study is a Research and Development (R&D) study with the ADDIE development model which includes five stages, namely (1) product analysis; (2) product design; (3) product development; (4) product implementation; and (5) product evaluation. The results of the research on the development of e-module poetry reading teaching materials show that the needs of students and teachers for poetry teaching materials in the form of e-modules are very necessary in supporting and improving the quality of poetry reading learning. The development design is in the form of an initial section starting from the book cover to the table of contents, then the learning activity section contains learning activities in training and guiding students in poetry reading activities, and the closing section is evaluation. The development of this teaching material has been tested by experts in terms of language, design, and material with practical and valid results (0.75) teaching materials are ready to be used by students. Product implementation is carried out on students by looking at student responses to the teaching materials used which are practical and ready to be used. Evaluation of teaching materials is used through the results of the initial trial and final trial of learning in poetry reading learning (t-count > t-table or 4.59 > 1.70).